Is Axillary Sonographic Staging Less Accurate in Invasive Lobular Breast Cancer Than in Ductal Breast Cancer?. (1st October 2014) - Sankaye, Prashant; Chhatani, Sharmila; Porter, Gareth; Steel, Jim; Doyle, Sarah
Abstract : Objectives: The purpose of this study was to determine whether axillary sonography is less accurate in invasive lobular breast cancer than in ductal breast cancer. Methods: Patients with invasive breast cancer were retrospectively identified from histologic records from 2010 to 2012. Staging axillary sonograms from 96 patients with primary breast cancer in each of 2 subgroups, invasive lobular carcinoma (ILC) and invasive ductal carcinoma (IDC), were reviewed. Preoperative sonographically guided 14‐gauge core biopsy was performed on morphologically abnormal lymph nodes. Results: Thirty‐one of 96 patients (32%) in each subgroup were node positive on final postoperative histopathologic analysis. Axillary staging sensitivity was 17 of 31 patients (54%) in the IDC subgroup and 15 of 31(48%) in the ILC subgroup. Further analysis of the data showed no statistically significant differences between these subgroups. Conclusions: We found that there was no statistically significant difference in the accuracy of axillary sonographic staging between ILC and IDC.